Diaphragm, battery and electric equipment
By using a foamed layer diaphragm made of a melt blend of polymethyl methacrylate and polyvinylidene fluoride in lithium-ion batteries, the safety problems of fire and explosion of the battery in overcharge and thermal runaway states are solved, and higher safety performance is achieved.
Patent Information
- Application Number
- CN202510040841.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Lithium-ion batteries are prone to fire and explosion in electrical and thermal abuse, mainly due to the loss of function of the diaphragm in high temperature or overcharge state, resulting in the continuous increase in the internal temperature of the battery.
A diaphragm is designed, which comprises a base film and a foamed layer made of a melt blend of polymethyl methacrylate and polyvinylidene fluoride at a foaming temperature between 110°C and 170°C. The composite particles effectively expand during the initial stage of overcharging or thermal runaway to protect the battery.
Through the expansion of the diaphragm, the battery overcharge time is reduced, the explosion-proof valve is opened in advance, the heat release is reduced, and the battery's safety performance is improved in the overcharge and thermal runaway state.
Smart Images

Figure CN119833892A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a diaphragm, a battery and an electrical device. Background Art
[0002] When lithium-ion batteries are used under electrical abuse (such as rapid charge and discharge) and thermal abuse (such as overheating), they will trigger a series of side reactions and release a large amount of heat in a short period of time, which will cause the internal temperature of the battery to continue to rise, and eventually cause a fire, resulting in serious safety problems. Common safety problems of lithium-ion batteries mainly occur in the diaphragm, which loses its function under battery abuse. Specifically, external extrusion, overcharge / discharge and uncontrollable lithium dendrite growth can cause the diaphragm to puncture and rupture, while diaphragm pore blockage, diaphragm shrinkage due to excessive internal temperature and melting rupture can all cause safety problems such as combustion and explosion, resulting in poor battery safety performance. Summary of the invention
[0003] In view of this, the present application provides a diaphragm, a battery and an electrical device, wherein the diaphragm can effectively expand when the battery is in an overcharged state or in the early stage of thermal runaway to protect the battery, so that the battery has good safety performance in an overcharged state or a thermal runaway state.
[0004] The present application provides a diaphragm, which includes: a base film and a foaming layer, wherein the foaming layer is arranged on one side of the base film, and the foaming layer includes composite particles, wherein the composite particles are a molten blend of polymethyl methacrylate and polyvinylidene fluoride, and the foaming temperature T of the composite particles is in the range of 110°C≤T≤170°C.
[0005] Furthermore, in the composite particles, the mass fraction of the polymethyl methacrylate is greater than the mass fraction of the polyvinylidene fluoride.
[0006] Furthermore, in the composite particles, the mass fraction a of the polyvinylidene fluoride is in the range of 10%≤a<50%.
[0007] Furthermore, the median particle size D of the composite particles is in the range of 0.5 μm ≤ D ≤ 1.5 μm.
[0008] Furthermore, after the composite particles are foamed, the expansion rate α of the composite particles is in the range of 1.5≤α≤15, wherein the expansion rate of the composite particles is the ratio of the volume of the composite particles after volume expansion to the volume of the composite particles before volume expansion.
[0009] Furthermore, the thickness h of the foaming layer is in the range of 1 μm≤h≤5 μm.
[0010] Furthermore, among the raw materials in the composite particles, the glass transition temperature T1 of the polymethyl methacrylate is in the range of 80°C≤T1≤120°C, and the melting temperature T2 of the polyvinylidene fluoride is in the range of 140°C≤T2≤160°C.
[0011] Furthermore, the composite particles are prepared by a melt-blending thermoforming process, and the thermoforming process includes at least one of extrusion molding, injection molding or calendering molding.
[0012] The present application provides a battery, which includes: a positive electrode plate, a diaphragm provided in the present application, a negative electrode plate and an electrolyte, wherein the diaphragm is arranged on one side of the positive electrode plate; the negative electrode plate is arranged on the side of the diaphragm away from the positive electrode plate; the electrolyte is used to infiltrate at least part of the positive electrode plate, the diaphragm and the negative electrode plate.
[0013] The present application also provides an electrical device, which includes: a device body and a battery provided in the present application, and the battery supplies power to the device body.
[0014] In the present application, the diaphragm includes a base film and a foaming layer, and the foaming layer includes composite particles, which are a blend of the polymethyl methacrylate and the polyvinylidene fluoride. In the composite particles, the polymethyl methacrylate is used as a foaming material. When the diaphragm is applied to a battery and the content of carbon dioxide in the battery is high, PMMA can absorb a large amount of carbon dioxide to expand the volume of the foaming layer and the diaphragm and touch the battery shell, thereby reducing the overcharge time of the battery to improve the safety performance of the battery under overcharge conditions. In addition, when the volume of the diaphragm expands and compresses the gas inside the battery, the air pressure inside the battery increases, which is conducive to opening the explosion-proof valve of the battery in advance, avoiding direct ignition due to excessive heat when the battery opens the valve, so that the battery also has better safety performance in the case of thermal runaway. In the composite particles, the role of the polyvinylidene fluoride is to assist PMMA in foaming. When the carbon dioxide in the environment of the composite particles reaches a certain concentration, the polyvinylidene fluoride crystallizes and the polyvinylidene fluoride produces a plasticizing effect during the crystallization process to promote the polymethyl methacrylate to form bubble pores, so that the composite particles have a faster foaming rate and a higher foaming ratio. The polyvinylidene fluoride and the polymethyl methacrylate are melt-blended to form the composite particles. Compared with the agglomerates formed by the polyvinylidene fluoride particles and the polymethyl methacrylate particles, the degree of mixing of the polyvinylidene fluoride and the polymethyl methacrylate in the composite particles is higher, so that the structure of the polyvinylidene fluoride and the structure of the polymethyl methacrylate change. The polymethyl methacrylate can reduce the crystallization temperature of the polyvinylidene fluoride and reduce the adsorption amount of carbon dioxide required to induce the crystallization of the polyvinylidene fluoride, so that the polyvinylidene fluoride is easier to crystallize, and finally the composite particles can be successfully foamed at a lower temperature. Through the melt blending of the polymethyl methacrylate and the polyvinylidene fluoride, the polymethyl methacrylate and the polyvinylidene fluoride affect each other, so that the foaming temperature T of the composite particles meets the range of 110°C≤T≤170°C. In other words, adding the polyvinylidene fluoride to the composite particles can effectively reduce the foaming temperature of the polymethyl methacrylate, so that when the battery is in an overcharged state or in the early stage of thermal runaway, the composite particles can be used as a foaming material under low pressure conditions, and timely foaming can shorten the battery overcharge time and open the explosion-proof valve in advance, reduce the concentration of combustible gas when the explosion-proof valve opens, and avoid excessive heat of the battery when the valve is opened, which directly ignites the battery, and at the same time improves the safety performance of the battery in the overcharged state and the thermal runaway state. Furthermore, the composite particles have good thermal insulation performance after foaming, which can block heat transfer when the battery has thermal runaway, reduce the probability of heat spread, and further improve the safety performance of the battery.When the foaming temperature T of the composite particles satisfies the range of 110°C≤T≤170°C, the foaming temperature of the composite particles is within a reasonable range. Compared with the solution of setting only the polymethyl methacrylate as the foaming material, the composite particles provided in the present application also include the polyvinylidene fluoride, and the polyvinylidene fluoride and the polymethyl methacrylate have a higher degree of fusion. The plasticizing effect of the polyvinylidene fluoride during crystallization can promote the polymethyl methacrylate to form bubble holes and foam. The polymethyl methacrylate can reduce the crystallization temperature of the polyvinylidene fluoride and reduce the amount of carbon dioxide adsorption that induces the crystallization of the polyvinylidene fluoride, so that the composite particles can foam rapidly when the temperature of the battery is abnormal. When the battery is in an overcharged or overheated state, the composite particles can expand in time to realize the early opening of the battery valve and reduce the heat when the explosion-proof valve is opened, so that the battery has better safety performance in the overcharge state and can reduce the probability of thermal runaway of the battery. When the foaming temperature of the composite particles is too low, the composite particles may foam prematurely and cause the battery to open the valve, reducing the reliability of the battery. When the foaming temperature of the composite particles is too high, the composite particles absorb carbon dioxide and expand too late, and cannot expand in time to reduce the damage to the battery caused by overcharging and thermal runaway, and the safety performance of the battery is poor. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 A simplified structural diagram of a battery according to an embodiment of the present application;
[0017] Figure 2 This is a schematic structural diagram of a diaphragm according to an embodiment of the present application;
[0018] Figure 3 A scanning electron microscope spectrum of agglomerates formed by directly dispersing and blending the polymethyl methacrylate and the polyvinylidene fluoride in a raw material;
[0019] Figure 4 A scanning electron microscope spectrum of the composite particles of an embodiment of the present application;
[0020] Figure 5 A schematic diagram of a foaming process of a foaming layer in a battery according to an embodiment of the present application;
[0021] Figure 6 This is a schematic diagram of the foaming principle of composite particles according to an embodiment of the present application;
[0022] Figure 7 This is a schematic structural diagram of a diaphragm according to another embodiment of the present application;
[0023] Figure 8 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application;
[0024] Fig. 9 This is a circuit block diagram of an electrical device according to an embodiment of the present application.
[0025] Description of reference numerals:
[0026] 100 - diaphragm, 110 - base film, 120 - foaming layer, 121 - composite particles, 130 - heat-resistant coating, 200 - battery, 210 - positive electrode sheet, 220 - negative electrode sheet, 230 - electrolyte, 240 - shell, 250 - top cover, 260 - receiving chamber, 300 - electrical equipment, 310 - equipment body. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0028] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0029] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0030] When lithium-ion batteries are used under electrical abuse (such as rapid charge and discharge) and thermal abuse (such as overheating), they will trigger a series of side reactions and release a large amount of heat in a short period of time, causing the internal temperature of the battery to continue to rise, eventually causing a fire and causing serious safety problems. Common safety problems of lithium-ion batteries mainly occur in the electrolyte and diaphragm. The diaphragm loses its function under battery abuse. Specifically, external extrusion, overcharge / discharge and uncontrollable lithium dendrite growth can cause the diaphragm to puncture and rupture, while diaphragm pore blockage, diaphragm shrinkage due to excessive internal temperature and melting and rupture can all cause safety problems such as combustion and explosion, resulting in poor battery safety performance.
[0031] At present, the most widely used polyolefin microporous membranes in lithium-ion batteries, such as polyethylene (PE) and polypropylene (PP), have low melting points, which makes the thermal stability of the diaphragm poor. When the battery temperature is too high, the polyolefin microporous membrane will shrink thermally, and the mechanical properties will drop sharply, eventually leading to a short circuit in the battery. The current patents mainly aim to improve the overcharge safety of lithium-ion batteries by adding special additives to the electrolyte, establishing a self-protection mechanism inside the battery, or coating the surface of the diaphragm with a layer of low-melting-point polymer coating to make it closed at high temperatures, thereby increasing polarization and shortening the overcharge time to improve overcharge safety. For thermal runaway, the heat resistance of the diaphragm is enhanced by introducing a high-heat-resistant coating to avoid internal short circuits in the battery due to thermal shrinkage and melting of the diaphragm after thermal runaway, which may cause fires, explosions and other dangers. However, none of the above improvement ideas can simultaneously improve the safety performance of lithium-ion batteries during overcharge and thermal runaway.
[0032] The inventors have found through research that when the battery is in the condition of electrical abuse or thermal abuse, side reactions are likely to occur between the positive electrode plate and the electrolyte, and between the negative electrode plate and the electrolyte, thereby releasing a large amount of heat, a large amount of flammable and toxic gases. The gas released by the battery heat is composed of a variety of combustible components, which is an important cause of fire and explosion in thermal safety tests. The composition of the gas is related to the positive electrode material and SOC value of the battery, but the main components are similar, including but not limited to: carbon dioxide CO2, hydrogen H2, carbon monoxide CO, and small molecule hydrocarbon substances. If the positive electrode material of the positive electrode plate is lithium iron phosphate (LFP), CO2 accounts for more than 50% of the gas production. In the description of this application, the gas formed is carbon dioxide as an example for description, which should not be understood as the gas produced by the side reactions between the positive electrode plate and the electrolyte, and between the negative electrode plate and the electrolyte is only carbon dioxide.
[0033] The inventor has found through research that when the electrolyte in the battery reacts with the positive electrode and / or the negative electrode and generates gas, as the gas gradually increases, the pressure inside the battery gradually increases until the safety valve opens, and the combustible gas is sprayed and mixed with the oxygen-containing air in the environment. Once the concentration reaches its flammable limit, it is very easy to be ignited by the high-temperature battery surface and the sprayed high-temperature particles. The combustion of the gas will further ignite the electrolyte and cause thermal runaway of adjacent batteries, causing the fire to spread and expand.
[0034] See also Figure 1 The present application provides a battery 200, which includes: a positive electrode sheet 210, a diaphragm 100 provided in the present application, a negative electrode sheet 220 and an electrolyte 230, wherein the diaphragm 100 is arranged on one side of the positive electrode sheet 210; the negative electrode sheet 220 is arranged on the side of the diaphragm 100 away from the positive electrode sheet 210; the electrolyte 230 is used to infiltrate at least part of the positive electrode sheet 210, the diaphragm 100 and the negative electrode sheet 220.
[0035] It can be understood that the positive electrode sheet 210 , the separator 100 , and the negative electrode sheet 220 are stacked, and the positive electrode sheet 210 , the separator 100 , and the negative electrode sheet 220 form an electrode assembly.
[0036] In this embodiment, the battery 200 includes the positive electrode sheet 210, the separator 100, the negative electrode sheet 220 and the electrolyte 230. The separator 100 includes: a base film 110 and a foaming layer 120, wherein the foaming layer 120 is disposed on one side of the base film 110, and the foaming layer 120 includes composite particles 121, wherein the composite particles 121 are a blend of the polymethyl methacrylate and the polyvinylidene fluoride, and the foaming temperature T of the composite particles 121 is in the range of 110°C≤T≤170°C, wherein the polymethyl methacrylate of the composite particles 121 and the polyvinylidene fluoride affect each other, and the polymethyl methacrylate can reduce the crystallization temperature of the polyvinylidene fluoride, and reduce the adsorption amount of carbon dioxide required to induce PVDF crystallization. The plasticizing effect of the polyvinylidene fluoride during the crystallization process is conducive to promoting the formation of bubble holes inside the polymethyl methacrylate, so that the composite particles 121 have a faster foaming rate and a higher foaming ratio. The polymethyl methacrylate and the polyvinylidene fluoride cooperate with each other, so that the foaming temperature of the composite particles 121 is low and the foaming performance is good. When the battery 200 is in an overcharged state or the temperature inside the battery 200 rises abnormally, the composite particles 121 can be foamed and expanded in time at the beginning of the thermal runaway of the battery 200 to shorten the overcharge time and reduce the excessive heat generated by the battery 200 when overcharged, and can make the explosion-proof valve open in advance, reduce the concentration of the combustible gas ejected when the explosion-proof valve is opened, so as to reduce the probability of the combustible gas and oxygen-containing air mixing and burning, thereby reducing the probability of thermal runaway of the battery 200. In addition, the foaming layer 120 can also be used as a heat insulating material after foaming and expansion to isolate the transfer of heat and reduce the probability of heat spread. The battery 200 has good safety performance in an overcharge state and a thermal runaway state.
[0037] Optionally, the battery 200 includes a shell 240, and the shell 240 is used to accommodate the positive electrode sheet 210, the separator 100, the negative electrode sheet 220 and the electrolyte 230. When the battery 200 is in a normal charge and discharge cycle, there is a gap between the electrode assembly and the shell 240. When the battery 200 is in an overcharge state, if the electrode assembly expands and touches the shell 240, the voltage of the battery 200 can quickly reach the overcharge cut-off voltage, thereby shortening the overcharge time of the battery 200.
[0038] It can be understood that, in the terminology of the present application, "overcharge" refers to the process of continuing to charge the battery 200 when the battery 200 is fully charged.
[0039] Optionally, the battery 200 further includes a top cover 250 and an explosion-proof valve (not shown), wherein the top cover 250 is connected to the housing 240 and together encloses a receiving chamber 260 to receive the positive electrode sheet 210, the diaphragm 100, the negative electrode sheet 220 and the electrolyte 230. The explosion-proof valve is disposed on the top cover 250, and when the air pressure in the receiving chamber 260 reaches the safety pressure threshold of the explosion-proof valve, the explosion-proof valve explodes and releases the gas inside the battery 200, thereby preventing the battery 200 from exploding and improving the safety performance of the battery 200.
[0040] It can be understood that, in the terminology of the present application, "the safety pressure threshold of the explosion-proof valve" refers to the pressure threshold at which the explosion-proof valve suddenly opens and releases the internal gas after being subjected to a certain pressure.
[0041] Please also see Figure 2 The present application provides a diaphragm 100, which includes: a base film 110 and a foaming layer 120, wherein the foaming layer 120 is arranged on one side of the base film 110, and the foaming layer 120 includes composite particles 121, wherein the composite particles 121 are a molten blend of polymethyl methacrylate (PMMA) and polyvinylidene fluoride (PVDF), and the foaming temperature T of the composite particles 121 is in the range of 110°C≤T≤170°C.
[0042] Optionally, in some embodiments, the diaphragm 100 includes a foaming layer 120, and the foaming layer 120 is arranged on one side of the base film 110; in other embodiments, the diaphragm 100 includes two foaming layers 120, and the two foaming layers 120 are arranged at opposite sides of the base film 110 at intervals.
[0043] It can be understood that the composite particles 121 are formed by melt blending the polymethyl methacrylate and the polyvinylidene fluoride, and the polymethyl methacrylate and the polyvinylidene fluoride have high compatibility.
[0044] It can be understood that, in the terminology of the present application, “foaming” refers to the introduction of bubbles or pore structures into a material, and the foaming of the composite particles 121 means that bubble pores are formed inside the composite particles 121 .
[0045] Specifically, the foaming temperature T of the composite particles 121 can be, but is not limited to, 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 158°C, 160°C, 165°C and 170°C, etc.
[0046] In this embodiment, the diaphragm 100 includes a base film 110 and a foaming layer 120, and the foaming layer 120 includes composite particles 121, which are a blend of polymethyl methacrylate and polyvinylidene fluoride. In the composite particles 121, the polymethyl methacrylate is used as a foaming material. When the diaphragm 100 is applied to the battery 200 and the content of carbon dioxide in the battery 200 is high, PMMA can absorb a large amount of carbon dioxide so that the volume of the foaming layer 120 and the diaphragm 100 expands and touches the housing 240 of the battery 200, thereby reducing the overcharge time of the battery 200 to improve the safety performance of the battery 200 under overcharge conditions. In addition, when the volume of the diaphragm 100 expands and compresses the gas inside the battery 200, the gas pressure inside the battery 200 increases, which is conducive to opening the explosion-proof valve of the battery 200 in advance, avoiding excessive heat when the battery 200 opens the valve and directly ignites, so that the battery 200 also has good safety performance under thermal runaway conditions. In the composite particles 121, the role of the polyvinylidene fluoride is to assist PMMA in foaming. When the carbon dioxide in the environment of the composite particles 121 reaches a certain concentration, the polyvinylidene fluoride crystallizes and the polyvinylidene fluoride produces a plasticizing effect during the crystallization process to promote the polymethyl methacrylate to form bubble pores, so that the composite particles 121 have a faster foaming rate and a higher foaming ratio. The polyvinylidene fluoride and the polymethyl methacrylate are melt-blended to form the composite particles 121. Compared with the agglomerates formed by the polyvinylidene fluoride particles and the polymethyl methacrylate particles, the polyvinylidene fluoride and the polymethyl methacrylate in the composite particles 121 are more mixed, so that the structure of the polyvinylidene fluoride and the structure of the polymethyl methacrylate change. The polymethyl methacrylate can reduce the crystallization temperature of the polyvinylidene fluoride and reduce the amount of carbon dioxide adsorbed to induce the crystallization of the polyvinylidene fluoride, so that the polyvinylidene fluoride is easier to crystallize, and finally the composite particles 121 can be successfully foamed at a lower temperature. By melt blending the polymethyl methacrylate and the polyvinylidene fluoride, the polymethyl methacrylate and the polyvinylidene fluoride influence each other, so that the foaming temperature T of the composite particles 121 satisfies the range of 110°C≤T≤170°C. In other words, adding the polyvinylidene fluoride to the composite particles 121 can effectively reduce the foaming temperature of the polymethyl methacrylate, so that when the battery 200 is in an overcharged state or in the early stage of thermal runaway, the composite particles 121 can be used as a foaming material under low pressure conditions, and timely foaming can shorten the overcharge time of the battery 200 and open the explosion-proof valve in advance, reduce the concentration of combustible gas when the explosion-proof valve opens, and avoid excessive heat of the battery 200 when opening the valve, which directly ignites the battery 200, while improving the safety performance of the battery 200 in the overcharged state and the thermal runaway state.Furthermore, the composite particles 121 have good heat insulation performance after foaming, which can block heat transfer when thermal runaway occurs in the battery 200, reduce the probability of heat spread, and further improve the safety performance of the battery 200. When the foaming temperature T of the composite particles 121 satisfies the range of 110°C≤T≤170°C, the foaming temperature of the composite particles 121 is within a reasonable range. Compared with the solution of only setting the polymethyl methacrylate as the foaming material, the composite particles 121 provided in this embodiment also include the polyvinylidene fluoride, and the polyvinylidene fluoride and the polymethyl methacrylate have a high degree of fusion. The plasticization effect of the polyvinylidene fluoride during crystallization can promote the polymethyl methacrylate to form bubble holes and foam. The polymethyl methacrylate can reduce the crystallization temperature of the polyvinylidene fluoride and reduce the amount of carbon dioxide adsorption that induces the crystallization of the polyvinylidene fluoride, so that the composite particles 121 can foam rapidly when the temperature of the battery 200 is abnormal. When the battery 200 is in an overcharged state or an overheated state, the composite particles 121 can expand in time to enable the battery 200 to open the valve in advance and reduce the heat when the explosion-proof valve opens, so that the battery 200 has better safety performance in an overcharged state and can reduce the probability of thermal runaway of the battery 200. When the foaming temperature of the composite particles 121 is too low, the composite particles 121 may foam too early and cause the battery 200 to open the valve, reducing the reliability of the battery 200. When the foaming temperature of the composite particles 121 is too high, the composite particles 121 absorb carbon dioxide and expand too late, and cannot expand in time to reduce the damage to the battery 200 caused by overcharging and thermal runaway, and the safety performance of the battery 200 is poor.
[0047] Preferably, the foaming temperature T of the composite particles 121 is in the range of 115°C≤T≤135°C.
[0048] Specifically, the polymethyl methacrylate and the polyvinylidene fluoride are formed by melt blending, and PMMA is an amorphous polymer. The addition of PMMA can promote the rearrangement of PVDF molecular chains around the crystal nucleus, thereby promoting the crystallization of PVDF, so as to reduce the crystallization temperature of PVDF, increase the crystallization rate and widen the crystallization temperature range, and reduce the adsorption amount of carbon dioxide required to induce PVDF crystallization. The molten foaming process can eliminate the hindering effect of crystals on foaming, significantly widen the range of foaming temperature, and when PVDF is in a low melt strength and in a crystalline state, it is conducive to inducing the opening of PMMA. Furthermore, the plasticizing effect of PVDF is enhanced during the crystallization process, and the microphase or microcrystal of PVDF can promote the generation of bubble holes in PMMA, so that the composite particles 121 have a faster foaming rate and a higher foaming ratio. Furthermore, the polyvinylidene fluoride is relatively soft, and PVDF can also reduce the curing temperature of the composite particles 121 to reduce the viscoelasticity of the composite particles 121, thereby promoting the polymethyl methacrylate to absorb carbon dioxide and increase the solubility of the polymethyl methacrylate in carbon dioxide, so as to provide more sufficient gas for the polymethyl methacrylate to generate bubble pores, which is conducive to the formation of larger bubble pores.
[0049] Understandably, see Figure 3 , Figure 3 The morphology of the agglomerates formed by directly dispersing and blending the polymethyl methacrylate and the polyvinylidene fluoride in the raw materials is shown. Figure 3 It can be seen that the polymethyl methacrylate and the polyvinylidene fluoride are independent of each other. The polymethyl methacrylate cannot promote the reduction of the rearrangement of the polyvinylidene fluoride and cannot reduce the crystallization temperature of the polyvinylidene fluoride; the polyvinylidene fluoride cannot promote the formation of air bubbles in the polymethyl methacrylate through the plasticization effect during crystallization. Therefore, Figure 3 Although the polymethyl methacrylate in the agglomerate shown can also foam, its foaming temperature is high, its foaming efficiency is low, and its foaming time is long. When the battery 200 is in an overcharged state or in the early stage of thermal runaway, Figure 3 The agglomerates shown must reach a certain temperature before they begin to foam, and the foaming response speed is slow, and the foaming efficiency is low, and the battery 200 cannot be effectively protected. Figure 4 The morphology of the composite particles 121 provided in the embodiment of the present application is shown. The composite particles 121 are melt-blended by the polymethyl methacrylate and the polyvinylidene fluoride so that the polymethyl methacrylate and the polyvinylidene fluoride interact with each other. The composite particles 121 can start to foam at a lower temperature, and the foaming temperature satisfies the range of 110°C≤T≤170°C. The composite particles 121 have a higher foaming efficiency and can foam and expand in a shorter time to protect the battery 200.
[0050] Understandably, see Figure 5 , Figure 5 The foaming process of the foaming layer 120 is shown, which is as follows: in the first stage S1, the battery 200 is in a normal charge and discharge cycle; in the second stage S2, a side reaction occurs inside the battery 200 to produce gas, and the carbon dioxide concentration inside the battery 200 increases. When the carbon dioxide concentration inside the battery 200 reaches a certain level, the composite particles 121 begin to absorb carbon dioxide. In the third stage S3, as the amount of carbon dioxide adsorbed by the composite particles 121 increases, the composite particles 121 expand and cause the volume of the diaphragm 100 to expand. The diaphragm 100 occupies a larger volume in the battery 200, thereby increasing the gas pressure in the battery 200. At this time, the composite particles 121 soften and are in a semi-solid state. In the fourth stage S4, as the air pressure in the battery 200 gradually increases to the safety pressure threshold of the explosion-proof valve, the explosion-proof valve opens. At this time, the concentration of the combustible gas such as carbon dioxide released is low, which can prevent the concentration of the combustible gas from reaching the flammable limit concentration range during pressure release and directly burning to cause thermal runaway. In addition, the air pressure inside the battery 200 is reduced, and carbon dioxide can form bubble holes inside the PMMA of the composite particles 121, realizing the foaming process of the composite particles 121. In the fifth stage S5, after the explosion-proof valve is depressurized, the temperature inside the battery 200 gradually decreases, and the composite particles 121 have good thermal insulation properties after foaming. At this time, the diaphragm 100 expands and sets, and plays a role in heat insulation, thereby slowing down the spread of heat.
[0051] It can be understood that the foaming temperature of the composite particles 121 satisfies the range of 110°C≤T≤170°C. Compared with the solution of only setting the polymethyl methacrylate as the foaming material, the foaming temperature of the composite particles 121 of this embodiment is lower, which can promote the third stage S3 and the fourth stage S4 of the foaming process of the foaming layer 120, so that when the battery 200 is in an overcharged state or the temperature rises abnormally, the overcharge time can be reduced, so that the explosion-proof valve explodes as soon as possible, and after the composite particles 121 expand, the diaphragm 100 can be used as a better heat insulation material to prevent the probability of heat spread. The composite particles 121 make the battery 200 have better safety performance in the overcharged state and can reduce the probability of thermal runaway of the battery 200. When the composite particles 121 are applied to the battery 200, the safety performance of the battery 200 during overcharge and thermal runaway can be improved at the same time.
[0052] It can be understood that in the foaming process of the composite particles 121, carbon dioxide is used as an initiator, see Figure 6 , Figure 6 The foaming principle of the composite particles 121 is shown as follows: In the second stage S2 of the foaming process of the foaming layer 120, i.e. Figure 6In the M1 stage, the composite particles 121 begin to absorb carbon dioxide; in the third stage S3 of the foaming process of the foaming layer 120, that is, Figure 6 In the M2 stage, as the temperature rises and the gas pressure increases, the composite particles 121 and the carbon dioxide form a homogeneous mixture; in the fourth stage S4 of the foaming process of the foaming layer 120, that is, Figure 6 In the M3 stage, after the explosion-proof valve is opened to release pressure, the gas pressure inside the battery 200 decreases, and carbon dioxide begins to nucleate inside the composite particles 121; in the fifth stage S5 of the foaming process of the foaming layer 120, that is, Figure 6 In the M4 stage, the temperature inside the battery 200 decreases, the carbon dioxide adsorbed on the composite particles 121 begins to grow, and eventually, pores are formed inside the composite particles 121 .
[0053] It is understandable that CO2, as an initiator of the composite particles 121, must reach a certain concentration of CO2 in the environment of the composite particles 121 before the composite particles 121 will foam. The CO2 inside the battery 200 comes from the side reaction between the electrolyte 230 and the positive electrode plate 210 and / or the negative electrode plate 220. Specifically, when the temperature inside the battery 200 is greater than 90°C, the side reaction intensifies and the rate of increase in the temperature inside the battery 200 accelerates. At this time, the composite particles 121 begin to foam under the action of CO2, and the foaming time is within 40s-300s, depending on the CO2 generation situation and speed.
[0054] It can be understood that the polymethyl methacrylate and the polyvinylidene fluoride are often used as bonding materials, and in the embodiment of the present application, the polymethyl methacrylate is matched with the polyvinylidene fluoride so that the polymethyl methacrylate has better foaming performance, and the composite particles 121 are used as ideal foaming materials. It is mainly reflected in the following aspects: First, compared with other common foaming materials such as polystyrene (PS), polyurethane (PU), etc., PMMA has a low carbon content, and thus has a lower heat release rate, a smaller heat release amount and a smaller smoke release amount, and will not deteriorate the safety of the battery 200. Second, PMMA has a high solubility in carbon dioxide, which can provide more sufficient gas for the nucleation and growth of bubble pores, and achieve a higher foaming ratio, so that the expansion ratio of the foaming layer 120 is within a reasonable range. Third, compared with traditional foaming materials such as PS, PU, etc., PMMA has more rigidity and toughness and is not easy to age. Fourth, PVDF and PMMA have good compatibility and can form a homogeneous blend. PVDF can reduce the viscoelasticity and curing temperature of the blend, and crystallization will occur during the adsorption stage. Its plasticizing effect can promote the growth of bubble pores, thereby reducing the optimal foaming temperature and producing a large-ratio foaming material under low-pressure conditions.
[0055] Optionally, in some embodiments, the preparation process of the composite particles 121 is: after the polymethyl methacrylate and the polyvinylidene fluoride are uniformly mixed according to a ratio, melt blending and extrusion are carried out at a high temperature, and then drying is carried out to obtain the composite particles 121.
[0056] Optionally, the foaming layer 120 is disposed on one side of the base film 110 by roller coating. Specifically, the composite particles 121 and the solvent are mixed, wherein the mass proportion of the composite particles 121 is 20% to 40%, and the mass proportion of the solvent is 60% to 80%. The composite particles 121 and the solvent are fully stirred and dispersed for 90 minutes, and a 180 lines / in micro-concave roller is selected for roller coating, and the foaming layer 120 with a thickness of 2 μm is obtained by extraction and drying. The solvent includes, but is not limited to, organic solvents such as N-methylpyrrolidone and dimethylacetamide. Among them, lines / in refers to the number of cells per inch (in) in length.
[0057] In some embodiments, in the composite particles 121 , the mass fraction of the polymethyl methacrylate is greater than the mass fraction of the polyvinylidene fluoride.
[0058] In the composite particles 121 provided in this embodiment, the mass fraction of the polymethyl methacrylate is greater than the mass fraction of the polyvinylidene fluoride, so that the composite particles 121 have more foaming materials. When the composite particles 121 are applied to the diaphragm 100 and assembled in the battery 200, if a side reaction occurs in the battery 200 and the concentration of carbon dioxide in the battery 200 gradually increases, the polymethyl methacrylate can absorb carbon dioxide and form bubble pores, so that the composite particles 121 have a large expansion degree, and the expansion degree of the diaphragm 100 is within a reasonable range, which is convenient for the electrode assembly to touch the shell 240, and the overcharge time is reduced while the explosion-proof valve is opened as soon as possible, so that the battery 200 has better safety performance in the overcharge state, and the probability of thermal runaway of the battery 200 can be reduced. Furthermore, when the explosion-proof valve is opened, the polyvinylidene fluoride can promote the carbon dioxide adsorbed in the polymethyl methacrylate to form larger bubble pores, so that the composite particles 121 have a faster foaming rate and a higher foaming ratio, so that the composite particles 121 have better thermal insulation properties after foaming, so that the diaphragm 100 can block heat transfer after the battery 200 is in thermal runaway, thereby reducing the probability of heat spread.
[0059] In some embodiments, in the composite particles 121 , the mass fraction a of the polyvinylidene fluoride is in the range of 10%≤a<50%.
[0060] It can be understood that in the composite particle 121 , the mass fraction of the polyvinylidene fluoride is the ratio of the mass of the polyvinylidene fluoride to the mass of the composite particle 121 .
[0061] It can be understood that by regulating the blending ratio of the polyvinylidene fluoride and the polymethyl methacrylate, the foaming temperature of the composite particles 121 can be regulated.
[0062] Specifically, the mass fraction a of the polyvinylidene fluoride can be but is not limited to 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48% and 49%, etc.
[0063] In the composite particles 121 provided in this embodiment, when the mass fraction a of the polyvinylidene fluoride satisfies the range of 10%≤a<50%, the mass fraction of the polyvinylidene fluoride and the mass fraction of the polymethyl methacrylate are both within a reasonable range. Polymethacrylic acid, as an amorphous polymer, can promote the rearrangement of the polyvinylidene fluoride molecular chain around the crystal nucleus and promote the crystallization of PVDF, so as to reduce the crystallization temperature of PVDF, increase the crystallization rate and widen the crystallization temperature range, and reduce the adsorption amount of carbon dioxide required to induce PVDF crystallization. The microphase or microcrystal of the polyvinylidene fluoride during the crystallization process can promote the generation of air bubbles in PMMA, so that the composite particles 121 can be foamed at a lower temperature and can form larger air bubbles, so that the composite particles 121 have better thermal insulation performance. When the battery 200 is in an overcharged state or thermal runaway, the composite particles 121 can foam and expand in time and shorten the overcharge time, and cause the explosion-proof valve to explode in advance, so as to reduce the probability of thermal runaway of the battery 200. When the mass fraction of the polyvinylidene fluoride is too large, the mass content of the polyvinylidene fluoride in the melt blend formed by the polyvinylidene fluoride and the polymethyl methacrylate is too high, and the mass content of the polymethyl methacrylate is too low. On the one hand, the polymethyl methacrylate is the main foaming material, and its content reduction means that the foaming performance of the composite particles 121 is weakened. On the other hand, the function of the polymethyl methacrylate in reducing the crystallization temperature of the polyvinylidene fluoride is weakened, so that the polyvinylidene fluoride crystallizes only at a higher temperature and in an environment with a high carbon dioxide content, which in turn weakens the function of the polyvinylidene fluoride in forming bubble pores, and finally makes the foaming temperature of the composite particles 121 too high. When the foaming temperature of the composite particles 121 is too high, the composite particles 121 absorb carbon dioxide and expand too late, and cannot expand in time to reduce the damage to the battery 200 caused by overcharging and thermal runaway, and the safety performance of the battery 200 is poor. When the mass fraction of the polyvinylidene fluoride is too small, the mass content of the polyvinylidene fluoride in the melt blend formed by the polyvinylidene fluoride and the polymethyl methacrylate is too low, and the plasticizing effect of the polyvinylidene fluoride in the crystallization process is weak, and it is difficult to enhance the nucleation of the bubble pores in the polymethyl methacrylate, so that the rate of bubble pore formation in the polymethyl methacrylate is low. When the battery 200 is overcharged or the temperature is too high, the composite particles 121 are difficult to foam quickly, so that the safety performance of the battery 200 in an overcharged state or a thermal runaway state is still poor.Therefore, by regulating the mass fraction of the polyvinylidene fluoride and the mass fraction of the polymethyl methacrylate in the composite particles 121, as well as controlling the compatibility of the polyvinylidene fluoride and the polymethyl methacrylate, the foaming temperature of the composite particles 121 can be within a reasonable range. When the concentration of the gas in the battery 200 exceeds the normal concentration, and / or the temperature inside the battery 200 exceeds the normal operating temperature, the composite particles 121 can foam and expand in time, reducing the overcharge time and enabling the battery 200 to open the valve in advance, thereby making the battery 200 have better safety performance in the overcharge state and reducing the probability of thermal runaway of the battery 200.
[0064] Preferably, in the composite particles 121, the mass fraction a of the polyvinylidene fluoride is in the range of 20%≤a≤40%. Specifically, the mass fraction a of the polyvinylidene fluoride may be, but is not limited to, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38% and 40%.
[0065] Optionally, in the composite particles 121, the mass fraction b of the polymethyl methacrylate is in the range of 50%≤b<90%. Specifically, the mass fraction b of the polymethyl methacrylate may be, but is not limited to, 50%, 55%, 60%, 65%, 68%, 70%, 75%, 80%, 85% and 90%.
[0066] In some embodiments, the median particle size D of the composite particles 121 is in the range of 0.5 μm ≤ D ≤ 1.5 μm.
[0067] Specifically, the median particle size D of the composite particles 121 may be, but is not limited to, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, etc.
[0068] In this embodiment, when the median particle size D of the composite particles 121 satisfies the range of 0.5 μm ≤ D ≤ 1.5 μm, the median particle size of the composite particles 121 is within a reasonable range. On the one hand, when the battery 200 is in an overcharged state or the temperature inside the battery 200 rises abnormally, the composite particles 121 foam and expand, and the volume after expansion is within a reasonable range, which can make the electrode assembly touch the housing 240 to shorten the overcharge time and avoid generating too much heat, and can make the explosion-proof valve open in advance to discharge the combustible gas in the battery 200, thereby reducing the probability of thermal runaway of the battery 200. On the other hand, it can avoid the composite particles 121 having a too small median particle size to increase the processing difficulty, and it can avoid the composite particles 121 having a too large median particle size to make the thickness of the foaming layer 120 too large, thereby avoiding increasing the internal resistance of the battery 200 and reducing the performance of the battery 200. When the median particle size of the composite particles 121 is too large, when the foaming layer 120 is disposed on one side of the base film 110, it becomes more difficult to coat the composite particles 121 on one side of the base film 110 and form the foaming layer 120, and the thickness of the foaming layer 120 is too large, which affects the electrical performance of the electrode assembly. When the median particle size of the composite particles 121 is too small, on the one hand, the composite particles 121 may block the pores of the base film 110, increasing the impedance of active ion transmission in the battery 200. On the other hand, the processing of the composite particles 121 with too small a median particle size is difficult, and the smaller the median particle size of the composite particles 121 and the smaller the degree of expansion during foaming, the smaller the volume of the composite particles 121 will be even after successful foaming, resulting in a smaller volume of the diaphragm 100 after expansion, which may make it difficult to resist the shell 240 and shorten the overcharge time of the battery 200, and it is also difficult to open the valve in advance, thereby reducing the safety performance of the battery 200 when the composite particles 121 are applied to the diaphragm 100 and assembled in the battery 200.
[0069] In some embodiments, after the composite particle 121 is foamed, the expansion rate α of the composite particle 121 is in the range of 1.5≤α≤15, wherein the expansion rate of the composite particle 121 is the ratio of the volume of the composite particle 121 after volume expansion to the volume of the composite particle 121 before volume expansion.
[0070] It can be understood that the expansion ratio of the composite particles 121 can represent the foaming ratio of the composite particles 121 .
[0071] Specifically, the expansion rate α of the composite particles 121 can be, but is not limited to, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 6.5, 6.8, 7, 7.5, 8, 8.6, 9, 10, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5 and 15, etc.
[0072] In this embodiment, when the expansion rate α of the composite particles 121 satisfies the range of 1.5≤α≤15, the expansion rate of the composite particles 121 is within a reasonable range, and when the battery 200 is in an overcharged state or the temperature in the battery 200 rises abnormally, the composite particles 121 foam and expand, and the volume of the composite particles 121 after expansion is within a reasonable range, so that the volume of the diaphragm 100 after expansion is also within a reasonable range, and the electrode assembly touches the shell 240 of the battery 200 to shorten the overcharge time of the battery 200, thereby improving the safety performance of the battery 200 in the overcharge state. At the same time, after the diaphragm 100 expands, it occupies more volume of the receiving cavity 260, increases the pressure in the receiving cavity 260, and quickly reaches the safety pressure threshold of the explosion-proof valve, and the explosion-proof valve opens to avoid the continuous accumulation of heat inside the battery 200, reducing the risk of thermal runaway of the battery 200, and ultimately improving the safety performance of the battery 200 in the thermal runaway state. When the expansion rate of the composite particles 121 is too large, the explosion-proof valve may be opened prematurely, reducing the reliability of the battery 200. When the expansion rate of the composite particles 121 is too small, when the battery 200 is in an overcharged state or the temperature in the battery 200 rises abnormally, even if the composite particles 121 foam and expand, the volume of the composite particles 121 after expansion is small, so that the volume of the diaphragm 100 after expansion is still small, and the electrode assembly is difficult to touch the shell 240 of the battery 200, making it difficult for the battery 200 to shorten the overcharge time of the battery 200 and improve the safety performance of the battery 200 in the overcharge state. At the same time, the volume of the diaphragm 100 occupied by the receiving cavity 260 after expansion is small, and it is difficult to increase the pressure in the receiving cavity 260 to quickly reach the safety pressure threshold of the explosion-proof valve. In other words, it is difficult to open the explosion-proof valve in advance, which leads to the continuous accumulation of heat inside the battery 200, increases the risk of thermal runaway of the battery 200, and reduces the safety performance of the battery 200 in the thermal runaway state.
[0073] Preferably, the expansion rate α of the composite particles 121 is in the range of 2≤α≤10.
[0074] In some embodiments, the thickness h of the foaming layer 120 is in the range of 1 μm≤h≤5 μm.
[0075] Specifically, the thickness h of the foaming layer 120 can be, but is not limited to, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.7 μm, 2.9 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, and 5 μm, etc.
[0076] In this embodiment, when the thickness h of the foaming layer 120 satisfies the range of 1μm≤h≤5μm, the thickness of the foaming layer 120 is within a reasonable range. On the first hand, when the battery 200 is in an overcharged state or the temperature inside the battery 200 rises abnormally, the composite particles 121 foam and expand and the volume after expansion is within a reasonable range. Then, the volume of the foaming layer 120 after foaming and expansion is within a reasonable range, and the electrode assembly is able to touch the shell 240 to shorten the overcharge time and prevent the battery 200 from generating excessive heat in the overcharged state. The foaming layer 120 expands and squeezes the air in the receiving cavity 260, so that the air pressure in the receiving cavity 260 increases to the safety pressure threshold of the battery 200, so that the explosion-proof valve opens in advance to discharge the combustible gas in the battery 200, thereby reducing the probability of thermal runaway of the battery 200. On the second aspect, the volume of the foaming layer 120 after expansion is within a reasonable range, so that the diaphragm 100 can be used as an ideal heat insulation material. Even if the battery 200 has thermal runaway, the diaphragm 100 can effectively block heat transfer and reduce the probability of heat spread. Therefore, when the thickness of the foaming layer 120 is within a reasonable range, it can simultaneously improve the safety performance of the battery 200 in the overcharge state and the thermal runaway state, and does not affect the safety performance of the battery 200, so that the battery 200 has better performance and a longer service life. When the thickness of the foaming layer 120 is too large, the impedance of the active ions in the battery 200 passing through the diaphragm 100 is increased during the normal charge and discharge cycle of the battery 200, and the internal resistance of the battery 200 is increased, thereby reducing the energy efficiency and performance of the battery 200. When the thickness of the foaming layer 120 is too small, when the battery 200 is in an overcharged state or the temperature inside the battery 200 rises abnormally, even if the composite particles 121 foam and expand, the expansion degree of the foaming layer 120 is still too small, and the volume of the diaphragm 100 after expansion is still small. It may be difficult to resist the shell 240 and shorten the overcharge time of the battery 200. It is also difficult to open the valve in advance, thereby reducing the safety performance of the battery 200 when the composite particles 121 are applied to the diaphragm 100 and assembled in the battery 200.
[0077] Optionally, the base film 110 may be, but is not limited to, a polyethylene base film 110 or a polypropylene base film 110 , and the thickness of the base film 110 is in a range of 7 μm to 20 μm.
[0078] See also Figure 7 Optionally, the diaphragm 100 further includes a heat-resistant coating 130, which is disposed between the base film 110 and the foaming layer 120 to isolate the heat transfer between the base film 110 and the foaming layer 120. The heat-resistant coating 130 may be, but is not limited to, a ceramic layer, a polyimide layer, a cellulose layer, etc. The thickness of the heat-resistant coating 130 ranges from 2 μm to 5 μm.
[0079] In some embodiments, among the raw materials in the composite particles 121, the glass transition temperature T1 of the polymethyl methacrylate is in the range of 80°C≤T1≤120°C, and the melting temperature T2 of the polyvinylidene fluoride is in the range of 140°C≤T2≤160°C.
[0080] Specifically, the glass transition temperature T1 of the polymethyl methacrylate can be, but is not limited to, 80°C, 82°C, 85°C, 86°C, 88°C, 90°C, 92°C, 95°C, 98°C, 100°C, 102°C, 105°C, 106°C, 108°C, 110°C, 112°C, 115°C, 118°C and 120°C, etc.
[0081] Specifically, the melting temperature T2 of the polyvinylidene fluoride may be, but is not limited to, 140°C, 142°C, 145°C, 146°C, 148°C, 150°C, 152°C, 153°C, 155°C, 157°C, 158°C, 160°C, etc.
[0082] In this embodiment, when the glass transition temperature T1 of the polymethyl methacrylate satisfies the range of 80°C≤T1≤120°C and the melting temperature T2 of the polyvinylidene fluoride satisfies the range of 140°C≤T2≤160°C, the melting temperature of the composite particles 121 is within a reasonable range. The composite particles 121 are in a molten state so that the degree of fusion of the polymethyl methacrylate and the polyvinylidene fluoride is high, and the polymethyl methacrylate and the polyvinylidene fluoride influence each other so that the foaming temperature of the composite particles 121 is within a reasonable range. When the battery 200 is in an overcharged state or the temperature in the battery 200 rises abnormally, the composite particles 121 can foam and expand in time to shorten the overcharge time and open the explosion-proof valve early, thereby improving the safety performance of the battery 200 in an overcharged state and in a thermal runaway state.
[0083] In some embodiments, the composite particles 121 are prepared by a melt-blending thermoforming process, wherein the thermoforming process includes at least one of extrusion molding, injection molding, or calendering molding.
[0084] In this embodiment, the composite particles 121 are prepared by a hot forming process of melt blending, which is conducive to making the polymethyl methacrylate and the polyvinylidene fluoride have a higher compatibility. The polymethyl methacrylate and the polyvinylidene fluoride affect each other. The polymethyl methacrylate can reduce the crystallization temperature of the polyvinylidene fluoride and reduce the adsorption amount of carbon dioxide required to induce the crystallization of the polyvinylidene fluoride. The plasticizing effect of the polyvinylidene fluoride during crystallization is conducive to the formation of bubble holes by carbon dioxide inside the polymethyl methacrylate to improve the foaming rate and foaming ratio of the composite particles 121. In other words, when the composite particles 121 are formed by at least one of extrusion molding, injection molding or calendering molding, the composite particles 121 can foam quickly at a lower temperature. When the battery 200 is in an overcharged state or the temperature rises abnormally, the composite particles 121 can respond quickly, and the composite particles 121 foam and expand quickly to shorten the overcharge time and open the explosion-proof valve as soon as possible, thereby improving the safety performance of the battery 200 in an overcharged state and a thermal runaway state.
[0085] The technical solution of this application is further introduced in the following with multiple embodiments:
[0086] Example 1 to Example 4, Comparative Example 1 and Comparative Example 2:
[0087] 1. Preparation of the diaphragm 100:
[0088] (1) A base film 110 is provided.
[0089] (2) Coating a heat-resistant coating 130 on the surface of the base film 110: Deionized water, ammonium polyacrylate, sodium carboxymethyl cellulose (CMC1140), aluminum oxide powder (D50 is 600 nm) and lithium acrylate copolymer emulsion are mixed at a ratio of 55:0.08:0.8:40:
[0090] 1.2 Mix evenly and stir thoroughly to obtain the slurry of the heat-resistant coating 130. Select a 180 lines / in micro-concave roller for roller coating, and apply the slurry of the heat-resistant coating 130 to the surface of the base film 110 to obtain a heat-resistant coating 130 with a thickness of 2 μm.
[0091] (3) Coating a foaming layer 120 on the surface of the heat-resistant coating 130: After the polymethyl methacrylate and the polyvinylidene fluoride are uniformly mixed according to a ratio, they are added to a twin-screw extruder for melt blending and extrusion to obtain the composite particles 121 of Examples 1 to 4, Comparative Examples 1 and 2. The composite particles 121 and N-methylpyrrolidone are mixed in a mass ratio of 30:70 and stirred for 90 minutes. A 180 lines / in micro-concave roller is selected for roller coating, extraction, and drying to obtain a foaming layer 120 with a thickness of 2 μm, thereby making the diaphragm 100 of Examples 1 to 4, Comparative Examples 1 and 2.
[0092] The composite particles 121 of Example 1 are applied to the diaphragm 100 of Example 1, the composite particles 121 of Example 2 are applied to the diaphragm 100 of Example 2, the composite particles 121 of Comparative Example 1 are applied to the diaphragm 100 of Comparative Example 1, and so on.
[0093] The values of the mass fraction a of the polyvinylidene fluoride and the mass fraction b of the polymethyl methacrylate in the composite particles 121 of Examples 1 to 4, Comparative Examples 1 and 2 are shown in Table 1.
[0094] 2. Preparation of positive electrode sheet 210:
[0095] The positive electrode active material lithium iron phosphate, the positive electrode conductive agent conductive carbon black (SP), and the positive electrode binder polyvinylidene fluoride (PVDF) are dispersed in a solvent N-methyl-2-pyrrolidone (NMP) according to a ratio and mixed evenly to obtain a positive electrode slurry with a solid content of 60wt%. The positive electrode slurry is coated on the positive electrode collector (aluminum foil), and the coating weight of the positive electrode slurry is 300mg / 1540.25mm 2 After drying, cold pressing, slitting and cutting, the positive electrode sheet 210 is obtained.
[0096] It can be understood that the separator 100 of the embodiment of the present application is suitable for lithium iron phosphate system, and the material of the positive electrode plate 210 provided in the present application is only an example and should not be understood as being only applicable to the positive electrode plate 210 provided in the present application.
[0097] 3. Preparation of negative electrode sheet 220:
[0098] The negative electrode active material hard carbon, the negative electrode conductive agent conductive carbon black (SP), the negative electrode thickener carboxymethyl cellulose (CMC), the negative electrode binder styrene butadiene rubber (SBR) and asphalt are dispersed in deionized water according to a ratio and mixed evenly to obtain a negative electrode slurry with a solid content of 50wt%. The negative electrode slurry is coated on the negative electrode collector (copper foil). The coating weight of the negative electrode slurry is 144mg / 1540.25mm 2 After drying, cold pressing, slitting and cutting, the negative electrode sheet 220 is obtained.
[0099] It can be understood that the separator 100 of the embodiment of the present application is suitable for lithium iron phosphate system, and the material of the negative electrode plate 220 provided in the present application is only an example and should not be understood as being only applicable to the negative electrode plate 220 provided in the present application.
[0100] 4. Preparation of electrolyte 230:
[0101] In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate are mixed in a mass ratio of 1:1:1, and then the dried electrolyte lithium salt lithium hexafluorophosphate is dissolved in the solvent, and the mixture is evenly mixed to obtain the electrolyte 230. The composition of the electrolyte 230 is as follows: the solvent composition is ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a mass ratio of 1:1:1, and the lithium salt concentration is 1 mol / L.
[0102] 5. Preparation of Battery 200:
[0103] The prepared positive electrode sheet 210, separator 100, and negative electrode sheet 220 are stacked in order so that the separator 100 is located between the positive electrode sheet 210 and the negative electrode sheet 220, and the positive electrode sheet 210, separator 100, and negative electrode sheet 220 are wound to obtain an electrode assembly, and the electrode assembly is assembled into an outer package after welding the electrode ears, and after injecting the prepared electrolyte 230, the battery cell is packaged, allowed to stand, formed, shaped, and capacity tested, and finally implementation batteries 1 to 6 are prepared.
[0104] The diaphragm 100 of Example 1 is applied to the implementation battery 1, the diaphragm 100 of Example 2 is applied to the implementation battery 2, the diaphragm 100 of Comparative Example 1 is applied to the comparison battery 1, and so on.
[0105] Table 1 below shows the performance parameters of the electrolyte 230 of Examples 1 to 4, Comparative Examples 1 and 2.
[0106] Table 1: Performance parameters of the electrolyte 230 of Examples 1 to 4, Comparative Examples 1 and 2.
[0107]
[0108]
[0109] Battery 200 performance test:
[0110] The expansion temperature and expansion ratio of the diaphragm 100 of Examples 1 to 4, Comparative Examples 1 and 2, and the overcharge cut-off temperature of the battery 1 to 4, the comparative battery 1 and the comparative battery 2 were tested:
[0111] The diaphragm 100 is assembled into a soft-pack battery and a single-cell overcharge test is performed according to the national standard. The temperature corresponding to when the soft-pack battery 200 begins to expand is taken as the expansion temperature of the diaphragm 100, and the temperature when the voltage reaches 1.5 times the initial voltage is taken as the overcharge cut-off temperature, and the time is recorded. The thickness of the electrode assembly after the test is measured and compared with the thickness of the initial electrode assembly, and the thickness of the diaphragm 100 before and after expansion is converted to calculate the expansion ratio of the diaphragm 100.
[0112] In addition, observe whether the corresponding battery 200 has passed the overcharge test. Overcharge test judgment standard: after the overcharge is cut off, if the battery 200 does not catch fire or explode after being left to stand for 1 hour, and other parts except the explosion-proof valve are broken, the test result of the battery 200 is considered to have passed the test, otherwise it is judged to have failed the test.
[0113] It can be understood that the expansion ratio of the membrane 100 can represent the expansion ratio of the composite particles 121 , and the expansion ratio of the membrane 100 is positively correlated with the expansion ratio of the composite particles 121 .
[0114] It can be understood that the expansion temperature of the membrane 100 can represent the foaming temperature of the composite particles 121, and the expansion temperature of the membrane 100 corresponds to the foaming temperature of the composite particles 121. In other words, the foaming temperature of the composite particles 121 is equivalent to the expansion temperature of the membrane 100.
[0115] It can be understood that the overcharge cut-off temperature of the battery 200 represents the temperature of the battery 200 after the overcharge is cut off. The higher the overcharge cut-off temperature, the worse the safety performance of the corresponding battery 200 under overcharge.
[0116] The expansion temperature and expansion ratio of the diaphragm 100 of Examples 1 to 4, Comparative Examples 1 and 2 are shown in Table 2. The overcharge cutoff temperature and overcharge test results of Implementation Battery 1 to Implementation Battery 4, Comparative Battery 1 and Comparative Battery 2 are shown in Table 2.
[0117] Table 2 below shows the performance parameters of the separator 100 of Examples 1 to 4, Comparative Examples 1 and 2, and the performance parameters of Implementation Batteries 1 to 4, Comparative Batteries 1 and 2.
[0118] Table 2: Performance parameters of the separator 100 of Examples 1 to 4, Comparative Examples 1 and 2, and performance parameters of Implementation Cells 1 to 4, Comparative Cells 1 and 2.
[0119]
[0120] Please refer to Table 1 and Table 2. It can be seen from the data of Examples 1 to 4 and Comparative Examples 1 and 2 that the composite particles 121 of the diaphragm 100 of Examples 1 to 4 and Comparative Examples 1 and 2 are all melt blends of the polymethyl methacrylate and the polyvinylidene fluoride, so that the composite particles 121 have good foaming and expansion properties. The overcharge test results of Implementation Battery 1 to Implementation Battery 4 and Comparative Battery 1 and Comparative Battery 2 are all passed, which shows that when the polymethyl methacrylate and the polyvinylidene fluoride are melt blended, the polymethyl methacrylate and the polyvinylidene fluoride affect each other, so that the polymethyl methacrylate can reduce the crystallization temperature of the polyvinylidene fluoride, and the plasticization effect of the polyvinylidene fluoride during crystallization can promote the formation of bubble holes in the polymethyl methacrylate, thereby expanding the diaphragm 100 and resisting the shell 240 of the battery 200, so as to shorten the overcharge time and improve the safety performance of Implementation Battery 1 to Implementation Battery 4, Comparative Battery 1 and Comparative Battery 2 under overcharge.
[0121] However, by adjusting the mass ratio of the polymethyl methacrylate and the polyvinylidene fluoride in the composite particles 121, the foaming properties of the composite particles 121 can be controlled. Specifically, in the composite particles 121 of the diaphragms 100 of Examples 1 to 4, the mass fraction a of the polyvinylidene fluoride satisfies the range of 10%≤a<50%, the mass fraction a of the polyvinylidene fluoride in the composite particles 121 of the diaphragm 100 of Comparative Example 1 is too small, and the mass fraction a of the polyvinylidene fluoride in the composite particles 121 of the diaphragm 100 of Comparative Example 2 is too small, so that the expansion temperature of the implementing battery 1 to the implementing battery 4 is lower than the expansion temperature of the comparative battery 1 and the comparative battery 2, the expansion ratio of the implementing battery 1 to the implementing battery 4 is lower than the expansion ratio of the comparative battery 2, the overcharge temperature of the implementing battery 1 to the implementing battery 4 is lower than the overcharge temperature of the comparative battery 1 and the comparative battery 2, and the implementing battery 1 to the implementing battery 4 is lower than the overcharge temperature of the comparative battery 1 and the comparative battery 2. The overcharge time of cell 4 is less than that of comparison cell 1 and comparison cell 2, because: when the mass fraction of the polyvinylidene fluoride is within a reasonable range, polymethacrylic acid, as an amorphous polymer, can promote the rearrangement of the polyvinylidene fluoride molecular chain around the crystal nucleus, promote the crystallization of PVDF, reduce the crystallization temperature of PVDF, increase the crystallization rate and widen the crystallization temperature range, and reduce the adsorption amount of carbon dioxide required to induce PVDF crystallization. The microphase or microcrystal of the polyvinylidene fluoride during the crystallization process can promote the generation of air bubbles in PMMA, so that the composite particles 121 can be foamed at a lower temperature and can form larger air bubbles, so that the composite particles 121 have better thermal insulation performance. When the battery 200 is in an overcharged state or thermal runaway, the composite particles 121 can foam and expand in time and shorten the overcharge time, and cause the explosion-proof valve to explode in advance, so as to reduce the probability of thermal runaway of the battery 200. Therefore, the implementation batteries 1 to 4 have lower expansion temperatures and overcharge temperatures, and have larger expansion ratios, shorter overcharge times, and the implementation batteries 1 to 4 have higher safety performance in overcharge states and thermal runaway states. When the mass fraction of the polyvinylidene fluoride is too small, in the composite particles 121, the plasticizing effect of the polyvinylidene fluoride in the crystallization process is weak, and it is difficult to enhance the nucleation of the bubble pores in the polymethyl methacrylate, so that the rate of bubble pore formation in the polymethyl methacrylate is low, and the polyvinylidene fluoride is also difficult to crystallize at a lower temperature, thereby reducing the foaming temperature of the composite particles 121. Therefore, in the comparative battery 1, although the comparative battery 1 has a higher expansion ratio and a lower overcharge time, its expansion temperature is still high and the overcharge time is still long. When the mass fraction of the polyvinylidene fluoride is too large, the polymethyl methacrylate is used as the main foaming material, and its reduced content means that the foaming performance of the composite particles 121 is weakened, so that the expansion ratio of the comparative battery 2 is extremely low.On the other hand, the function of the polymethyl methacrylate in reducing the crystallization temperature of the polyvinylidene fluoride is weakened, so that the polyvinylidene fluoride can only crystallize at a higher temperature and in an environment with a higher carbon dioxide content, which in turn weakens the function of the polyvinylidene fluoride in forming bubble pores, and finally makes the foaming temperature of the composite particles 121 too high. Therefore, the expansion temperature and overcharge temperature of the comparative battery 2 are both higher, and the overcharge time is longer.
[0122] Furthermore, from the data of Examples 1 to 4, it can be seen that as the mass fraction of the polyvinylidene fluoride gradually increases, the corresponding expansion temperature of the battery 200 first decreases and then increases, the expansion multiple first increases and then decreases, the overcharge temperature first decreases and then increases, and the overcharge time first decreases and then increases. This shows that when the mass fraction of the polyvinylidene fluoride and the mass fraction of the polymethyl methacrylate are both within a reasonable range, the interaction between the polymethyl methacrylate and the polyvinylidene fluoride is better, so that the foaming temperature of the composite particles 121 satisfies the range of 110°C≤T≤170°C, and when the battery 200 is in an overcharge state or in the early stage of thermal runaway, the diaphragm 100 can protect the battery 200 to simultaneously improve the safety performance of the battery 200 in the overcharge state and the thermal runaway state.
[0123] See also Figure 8 and Fig. 9 The present application also provides an electrical device 300 , which includes: a device body 310 and a battery 200 provided in the present application, and the battery 200 supplies power to the device body 310 .
[0124] It can be understood that the battery 200 is electrically connected to the device body 310 .
[0125] In this embodiment, the diaphragm 100 includes the composite particles 121, and the composite particles 121 have a better foaming temperature range, so that the composite particles 121 can effectively foam and expand when the battery 200 is in an overcharge state or in the early stage of thermal runaway, so as to shorten the overcharge time and open the explosion-proof valve as soon as possible, so that the battery 200 has better safety performance in both the overcharge state and the thermal runaway state, and the battery 200 has a longer service life. When the battery 200 is applied to the electrical device 300, the battery 200 can provide stable power for the device body 310, which is conducive to improving the user experience.
[0126] Optionally, the power-consuming device 300 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 8 The electrical equipment 300 of the embodiment is an energy storage battery cabinet.
[0127] It can be understood that the electric device 300 described in this embodiment is merely a form of the electric device 300 used by the battery 200, and should not be understood as a limitation on the electric device 300 provided in this application, nor should it be understood as a limitation on the electric device 300 provided in each embodiment of this application.
[0128] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0129] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. A diaphragm, characterized in that: The diaphragm comprises: basement membrane; and A foaming layer is arranged on one side of the base film, the foaming layer comprises composite particles, the composite particles are a molten blend of the polymethyl methacrylate and the polyvinylidene fluoride, and the foaming temperature T of the composite particles is in the range of 110°C≤T≤170°C.
2. The diaphragm according to claim 1, characterized in that In the composite particles, the mass fraction of the polymethyl methacrylate is greater than the mass fraction of the polyvinylidene fluoride.
3. The diaphragm according to claim 2, characterized in that In the composite particles, the mass fraction a of the polyvinylidene fluoride is in the range of 10%≤a<50%.
4. The diaphragm according to claim 1, characterized in that The range of the median particle size D of the composite particles is: 0.5 μm≤D≤1.5 μm.
5. The diaphragm according to any one of claims 1 to 4, characterized in that: After the composite particles are foamed, the expansion rate α of the composite particles is in the range of 1.5≤α≤15, wherein the expansion rate of the composite particles is the ratio of the volume of the composite particles after volume expansion to the volume of the composite particles before volume expansion.
6. The diaphragm according to any one of claims 1 to 4, characterized in that The thickness h of the foaming layer is in the range of 1 μm≤h≤5 μm.
7. The diaphragm according to any one of claims 1 to 4, characterized in that Among the raw materials in the composite particles, the glass transition temperature T1 of the polymethyl methacrylate is in the range of 80°C≤T1≤120°C, and the melting temperature T2 of the polyvinylidene fluoride is in the range of 140°C≤T2≤160°C.
8. The diaphragm according to any one of claims 1 to 4, characterized in that The composite particles are prepared by a melt-blending thermoforming process, wherein the thermoforming process includes at least one of extrusion molding, injection molding or calendering molding.
9. A battery, characterized in that: The battery comprises: Positive electrode; The diaphragm according to any one of claims 1 to 8, wherein the diaphragm is disposed on one side of the positive electrode plate; A negative electrode plate, the negative electrode plate being disposed on a side of the diaphragm away from the positive electrode plate; and An electrolyte is used to soak at least a portion of the positive electrode sheet, the separator and the negative electrode sheet.
10. An electrical device, characterized in that: The electrical equipment includes: The device itself; and The battery of claim 9, wherein the battery is used to power the device body.
Citation Information
Patent Citations
Method for preparing high-strength nanometre reticular fibrous membrane
CN105932205A
PMMA / PVDF (Polymethyl Methacrylate / Polyvinylidene Fluoride) composite diaphragm and preparation method and application thereof
CN115207566A
PVDF-PMMA-coated Al2O3 composite material coated lithium ion battery diaphragm and preparation method thereof
CN115939659A